Structure of 3-oxoacyl-(acyl-carrier protein) synthase II from Thermus thermophilus HB8 - Bagautdinov, Bagautdin (International Union of Crystallography, 2008)
The β-ketoacyl-(acyl carrier protein) synthases (β-keto-ACP synthases; KAS) catalyse the addition of two-carbon units to the growing acyl chain during the elongation phase of fatty-acid synthesis. As key regulators of bacterial fatty-acid synthesis, they are promising targets for the development of new antibacterial agents. The crystal structure of 3-oxoacyl-ACP synthase II from Thermus thermophilus HB8 (TtKAS II) has been solved by molecular replacement and refined at 2.0 Å resolution. The crystal is orthorhombic, space group P2(1)2(1)2, with unit-cell parameters a = 72.07, b = 185.57, c = 62.52 Å, and contains one homodimer in the asymmetric unit. The subunits adopt the well known α-β-α-β-α thiolase fold that is common to ACP synthases. The structural and sequence similarities of TtKAS II to KAS I and KAS II enzymes of known structure from other sources support the hypothesis of comparable enzymatic activity. The dimeric state of TtKAS II is important to create each fatty-acid-binding pocket. Closer examination of KAS structures reveals that compared with other KAS structures in the apo form, the active site of TtKAS II is more accessible because of the ‘open’ conformation of the Phe396 side chain.